IGF1 Gene Therapy Reversed Cognitive Deficits and Restored Hippocampal Alterations After Chronic Spinal Cord Injury - Jure, Ignacio (2021)
The hippocampus is implicated in the generation of memory and learning, processes which involve extensive neuroplasticity. The generation of hippocampal adult-born neurons is particularly regulated by glial cells of the neurogenic niche and the surrounding microenvironment. Interestingly, recent evidence has shown that spinal cord injury (SCI) in rodents leads to hippocampal neuroinflammation, neurogenesis reduction, and cognitive impairments. In this scenario, the aim of this work was to evaluate whether an adenoviral vector expressing IGF1 could reverse hippocampal alterations and cognitive deficits after chronic SCI. SCI caused neurogenesis reduction and impairments of both recognition and working memories. We also found that SCI increased the number of hypertrophic arginase-1 negative microglia concomitant with the decrease of the number of ramified surveillance microglia in the hilus, molecular layer, and subgranular zone of the dentate gyrus. RAd-IGF1 treatment restored neurogenesis and improved recognition and working memory impairments. In addition, RAd-IGF1 gene therapy modulated differentially hippocampal regions. In the hilus and molecular layer, IGF1 gene therapy recovered the number of surveillance microglia coincident with a reduction of hypertrophic microglia cell number. However, in the neurogenic niche, IGF1 reduced the number of ramified microglia and increased the number of hypertrophic microglia, which as a whole expressed arginase-1. In summary, RAd-IGF1 gene therapy might surge as a new therapeutic strategy for patients with hippocampal microglial alterations and cognitive deficits such as those with spinal cord injury and other neurodegenerative diseases.